Chemical Composition and Antioxidant Activity of the Essential Oil and Methanolic Extract of Salvia multicaulis Vahl. - H Amiri (Institue of Medicinal Plants, ACECR, 2012)
Background: Salvia multicaulis is a permanent herb belongs to Lamiaceae family which wildely grows in most regions of Iran. This plant is used as flavour and tea.   Objectives: Investigation on the essential oil composition and antioxidant activity of Salvia multicaulis from Lorestan province and comparison of these with other regions.   Methods: The aerial parts of the plant were collected from Broujerd in Lorestan province. The air-dried samples were subjected to hydrodistillation using by Cleavenger apparatus for 2 h (in yield of 0.3%). The essential oil was analyzed by GC and GC/MS. The samples were subjected to screening for their possible antioxidant activity by using DPPH and β-carotene-linoleic acid assay   Results: Forty-two constituents were identified, accounting for 90.96% of total oil. The main components of this oil were bornyl acetate (18.58%), borneol (17.16%), camphor (13.75%), camphene (5.62%) and β-caryophyllene (5.85%).The samples were subjected to a screening for their possible antioxidant activities by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and β-carotene-linoleic acid assays. In general, in both method the methanolic extract exhibited greater antioxidant activities than essential oil. Conclusion: Antioxidants act as radical scavengers, inhibit lipid peroxidation and other free adical-mediated processes and are able to protect the human body as well as processed foods from oxidative damage attributed to the reaction of free radicals.